Efektivitas Implementasi Pelatihan Keterampilan Kerja Dalam Meningkatkan Kompetensi Calon Tenaga Kerja - Rizka, Muhammad Arief; Zulkipli, Zulkipli (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
This study aims to analyze the effectiveness level of the implementation of working skill training programs in the field of office administration in improving the competence of prospective workers in the Training Center (BLK) Mataram City. This research is an evaluative research by using quantitative descriptive method. The research instrument used is a questionnaire. Data analysis technique used in this research is descriptive statistical analysis. The results of this study indicated that the training implementation process aspect with the training instructor role indicator got the percentage 82.73%, the training material indicator was 78.76%, the training method indicator was 79.76%, while the result aspect follows the training with the cognitive domain indicator got the percentage 84, 92%, the affective field indicator was 81.34%, psychomotor domain indicator was 79.16%, while achievement goal aspect after work skill training got percentage 82,03%. Thus, it can be concluded that the effectiveness of the implementation of working skill training programs in the field of office administration in improving the prospective workers competence in the Training Center (BLK) Mataram has been effectively implemented.